2021
DOI: 10.47115/jshs.862496
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Nomophobia In Nurses And Its Effect On Job Satisfaction

Abstract: Amaç: Bu çalışma, çalışan hemşirelerde nomofobinin varlığı ve iş tatmini üzerine etkisini incelemek amacıyla yapılmıştır. Yöntem: Tanımlayıcı tipte yapılan bu araştırma da bir ilçe hastanesinde görev yapan ve akıllı telefon kullanıcısı olan 74 hemşire çalışmaya alınmıştır. Verilerin toplanmasında Kişisel Bilgi Formu, Nomofobi Ölçeği (NMP-Q) ve Minnesota İş Tatmini Ölçeği kullanılmıştır. Verilerin değerlendirilmesinde, yüzdelik, Independent Sample-t, Mann Whitney U ve ANOVA testleri kullanılmıştır. Bulgular: Ça… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…In the study conducted by Hosgor et al to identify the relationship between the nomophobia level and the perceived workload in nurses, it is stated that a large majority of the nurses had medium-level nomophobia (11). Likewise, in the study performed by Korkmaz and Aslan to assess whether nurses had nomophobia, it is put forward those nurses had medium-level nomophobia (5). On the other hand, in a study that analyzed the relationship between nurses' personality characteristics and nomophobia, it was identified that nurses had high-level nomophobia (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study conducted by Hosgor et al to identify the relationship between the nomophobia level and the perceived workload in nurses, it is stated that a large majority of the nurses had medium-level nomophobia (11). Likewise, in the study performed by Korkmaz and Aslan to assess whether nurses had nomophobia, it is put forward those nurses had medium-level nomophobia (5). On the other hand, in a study that analyzed the relationship between nurses' personality characteristics and nomophobia, it was identified that nurses had high-level nomophobia (25).…”
Section: Discussionmentioning
confidence: 99%
“…Prepared in light of the review of the relevant literature (5,16), the Personal Information Form had a total of 23 questions (7 questions about nurses' socio-demographic characteristics, 10 questions designed to analyze the work conditions at intensive care clinics, and 6 questions about the smartphone use).…”
Section: The Personal Information Formmentioning
confidence: 99%
See 1 more Smart Citation